2011
DOI: 10.1007/s00253-011-3692-6
|View full text |Cite
|
Sign up to set email alerts
|

2,4-DNT removal in intimately coupled photobiocatalysis: the roles of adsorption, photolysis, photocatalysis, and biotransformation

Abstract: The removal of 2,4-dinitrotoluene (2,4-DNT) by simultaneous UV-photo(cata)lysis and biodegradation was explored using intimately coupled photolysis/photocatalysis and biodegradation (ICPB) with two novel porous carriers. First, a porous ceramic carrier was used to attach the photocatalyst (TiO₂) on its exterior and accumulate biomass in its interior. UV irradiation alone decomposed 71% of the 2,4-DNT in 60 h, and TiO₂ catalyst improved the photolysis to 77%. Second, a macroporous sponge carrier was used to str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 34 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…The released SMP could contribute to the increment of DOC. As indicated by Wen et al, less adsorbable intermediates release could be another reason for DOC increment of UPCB. In this work, maleic acid should be the product less adsorbable to the sponge carrier, as it could be well degraded via photocatalysis alone; however, it turned out to accumulate either in the VPCB or the UPCB, whereas the attached biofilms occupied most of the sponge carriers’ adsorption positions.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The released SMP could contribute to the increment of DOC. As indicated by Wen et al, less adsorbable intermediates release could be another reason for DOC increment of UPCB. In this work, maleic acid should be the product less adsorbable to the sponge carrier, as it could be well degraded via photocatalysis alone; however, it turned out to accumulate either in the VPCB or the UPCB, whereas the attached biofilms occupied most of the sponge carriers’ adsorption positions.…”
Section: Resultsmentioning
confidence: 84%
“…These bioconsumable intermediates were degraded by the attached biomass in a single reactor. And then the ICPB process was investigated with the aim of enhancing the removal of phenolic organics and even complex compounds , from wastewater. It was found that the exterior face of the carrier cube was free of bacterial cells due to the participation of photocatalytic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The porous carriers involved in ICPB system mainly contain porous ceramic [ 14 , 15 ], cellulose [ 2 ] and the polyurethane sponge carriers [ 16 ]. Ceramic carriers have the advantage of strong stability, reusability and durability, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Following its proposal, ICPB technology has been successfully applied to the degradation of refractory organic compounds such as phenol [11][12][13], 2,4,5-trichlorophenol [10,14] 2, 4-diaminotoluene [15] and tetracycline [16,17] as well as printing and dyeing wastewater [18,19]. Most photocatalytic carriers are inorganic materials, such as activated carbon, zeolite, glass, ceramics, etc., which have good treatment effect [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Li G et al [15] used TiO 2 coated polyurethane sponge carrier to remove 2,4,5-trichlorophos (TCP), and successfully proved the feasibility and advantages of ICPB direct coupling system. Wen et al [16] prepared porous ceramic carrier under UV light to degrade 2,4-DNT, the degradation rate reached 78%. Yongming et al [14] designed an immobilized photocatalytic biofilm reactor based on a honeycomb ceramic carrier, which was very stable under UV light.…”
Section: Introductionmentioning
confidence: 99%